Synthesis, Physicochemical Characterization, and Cytotoxicity Assessment of CeO2 Nanoparticles with Different Morphologies. Issue 25 (5th July 2017) - Spezzati, Giulia; Fant, Kristina; Ahniyaz, Anwar; Lundin‐Johnson, Maria; Hensen, Emiel J. M.; Langermans, Harm; Hofmann, Jan P.
Abstract : With the growing use of nanomaterials, it is essential to carefully determine whether they represent a risk for potential users. So far, validated stand‐alone methods that allow a proper risk assessment are still rare. In the present study, the cytotoxicity of CeO2 nanoparticles has been assessed. For this purpose, a variety of well‐defined CeO2 nanoparticles has been prepared by using either hydrothermal synthesis or flame spray pyrolysis (FSP), resulting in nanoparticles of different morphologies and sizes. The FSP technique is known to produce particles of a very small size (in the range of nanometers), which can easily become airborne. We employed a characterization procedure that makes use of physicochemical techniques, comprising N2 physisorption, XRD, TEM, as well as ζ ‐potential and surface‐charge measurements. The cytotoxicity of the nanoparticles was evaluated in vitro on two different human lung cell lines (A549 and MRC‐5). The tests showed that, despite the differences in surface properties, size, and morphologies, neither of the CeO2 samples gave rise to a cytotoxic response. Abstract : CeO2 nanoparticles with different shapes and sizes were synthesized and tested with an array of physicochemical methods. Cytotoxicity tests on two lung cell lines were performed and no negative effect due to exposure to CeO2 nanoparticles was found.